Netnography as a methodological lens for uncovering heritage ambience: A case study of the Tlemcen medina - Ikram Khemies; Mohammed Nabil Ouissi; Walid Hamma (Urbani Izziv, 2025)

(untitled)
The concept of heritage ambience reconfigures cultural preservation by prioritizing multisensory experiences and human subjectivity, transcending static architectural analysis. However, capturing these intangible dimensions – rooted in sensory engagement, memory, and local narratives – remains methodologically challenging. This study employs netnography to decode interactions between sensory atmospheres and collective memory in historic urban spaces, using the medina in Tlemcen, Algeria, as a case study. Analysis of digital narratives, social media discourses, and community-generated content reveals how nonexpert knowledge reconstructs heritage values often marginalized by traditional conservation frameworks. The results demonstrate that the medina’s ambience is not merely a backdrop but a dynamic archive of lived experiences, where smells, sounds, and textures intertwine to shape cultural identity. This research advocates integrating local perspectives into protection strategies, challenging the hegemony of institutional approaches. By linking digital ethnography and sensory urbanism, it proposes a reproducible methodological framework for reimagining heritage as a living, participatory practice where the spirit of place thrives through community governance.